MEMBANGUN KECERDASAN INTRAPERSONAL MELALUI KEGIATAN INTERAKSI DI TK AL- KAUSAR - Nasution, Dinil Arifah; Sabila, Khairiyah; Siregar, Rheina Meisya; Aulia, Putri; Sit, Masganti (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2024)
Early childhood education at Al-Kautsar Kindergarten plays an important role in shaping children's responsibility towards themselves and their environment. However, children's responsibilities vary, with some children being able to take responsibility while others are not. Teachers at Al-Kautsar Kindergarten carry out various practices and constant reminders to develop children's responsibility, but challenges remain. In addition, intrapersonal intelligence in children at Al-Kautsar Kindergarten is not only about self-understanding, but also about interactions with other people. Therefore, parents can help develop children's intrapersonal intelligence by inviting them to participate in social activities. Apart from intrapersonal intelligence, interpersonal intelligence is also important to develop. Therefore, teachers can use various interactive methods and programs to stimulate children's intellectual development and critical thinking skills. At Al-Kautsar Kindergarten, indicators of intrapersonal intelligence include recognition and regulation of emotions, self-knowledge, ability to share, development of independence, and self-adjustment. The involvement of parents in early childhood education at Al-Kautsar Kindergarten is very important because they are the children's first educators and play a role in shaping children's development. One way to involve parents in learning is to involve them in weekend activities and ask them to share their experiences with children at school.